Cities for profit : the real estate turn in Asia's urban politics - Shatkin, Gavin (Cornell University Press, 2017)
Cities for Profit examines the phenomenon of urban real estate megaprojects in Asia--massive, privately built planned urban developments that have captured the imagination of politicians, policymakers, and citizens across the region. These controversial projects, embraced by elites, occasion massive displacement and have extensive social and economic impacts. Gavin Shatkin finds commonalities and similarities in dozens of such projects in Jakarta, Kolkata, and Chongqing. Shatkin is at the vanguard of urban studies in his focus on real estate. Just as cities are increasingly defined and remapped according to the value of the land under their residents' feet, the lives of city dwellers are shaped and constrained by their ability to keep up with rising costs of urban life. Scholars and policy and planning professionals alike will benefit from Shatkin's comprehensive research. Cities for Profit contains insights from more than 150 interviews, site visits to projects, and data from government and nongovernmental organization reports and data, urban plans, architectural renderings, annual reports and promotional materials of developers, and newspaper and other media accounts.